Heat stress increases muscle glycogen use but reduces the oxidation of ingested carbohydrates during exercise - Jentjens, R. L. P.; Wagenmakers, A. J. M.; Jeukendrup, A. E. (Journal of Applied Physiology, 2002)
The aim of the present study was to test the hypothesis that the oxidation rate of ingested carbohydrate (CHO) is impaired during exercise in the heat compared with a cool environment. Nine trained cyclists (maximal oxygen consumption 65 ± 1 ml · kg body wt1 · min1) exercised on two different occasions for 90 min at 55% maximum power ouptput at an ambient temperature of either 16.4 ± 0.2°C (cool trial) or 35.4 ± 0.1°C (heat trial). Subjects received 8% glucose solutions that were enriched with [U-13C]glucose for measurements of exogenous glucose, plasma glucose, liver-derived glucose and muscle glycogen oxidation. Exogenous glucose oxidation during the final 30 min of exercise was significantly (P < 0.05) lower in the heat compared with the cool trial (0.76 ± 0.06 vs. 0.84 ± 0.05 g/min). Muscle glycogen oxidation during the final 30 min of exercise was increased by 25% in the heat (2.07 ± 0.16 vs. 1.66 ± 0.09 g/min; P < 0.05), and liver-derived glucose oxidation was not different. There was a trend toward a higher total CHO oxidation and a lower plasma glucose oxidation in the heat although this did not reach statistical significance (P = 0.087 and P = 0.082, respectively). These results demonstrate that the oxidation rate of ingested CHO is reduced and muscle glycogen utilization is increased during exercise in the heat compared with a cool environment.